Development of Creative Industries as Regional Leaders in National Tourism Efforts Based on Geographical Indications - Rian Saputra (BESTUUR, 2020)
This study aims to examine and explain the role of various parties both government, business and community in synergy to develop Geographical Indications products as creative economic potential to develop national tourism based on regional superior products and Geographical Indications. This research is writing normative law using the legislative approach method. The results of the study show that the growth of the creative industry as a superior product based on geographical indications in Indonesia is quite rapid. Creative Industries as regional superior products based on geographical indications can be used and developed as a tool to attract tourists to visit Indonesia due to their unique characteristics or characteristics, and vice versa tourism has been made a partner by the Directorate General of Intellectual Property to promote Indications products Geographically owned by Indonesia at the global level or in every international tourism event. Keywords: Creative Industries, Geographical Indications, Tourism